Annexin A4 Is Dispensable for Hair Cell Development and Function - Li, Nana; Xi, Yuehui; Du, Haibo; Zhou, Hao; Xu, Zhigang (Frontiers in Cell and Developmental Biology, 2021)
Annexin A4 (ANXA4) is a Ca2+-dependent phospholipid-binding protein that is specifically expressed in the cochlear and vestibular hair cells, but its function in the hair cells remains unknown. In the present study, we first show that besides localizing on the plasma membrane, ANXA4 immunoreactivity is also localized at the tips of stereocilia in the hair cells. In order to investigate the role of ANXA4 in the hair cells, we established Anxa4 knockout mice using CRISPR/Cas9 technique. Unexpectedly, the development of both cochlear and vestibular hair cells is normal in Anxa4 knockout mice. Moreover, stereocilia morphology of Anxa4 knockout mice is normal, so is the mechano-electrical transduction (MET) function. Consistently, the auditory and vestibular functions are normal in the knockout mice. In conclusion, we show here that ANXA4 is dispensable for the development and function of hair cells, which might result from functional redundancy between ANXA4 and other annexin(s) in the hair cells.